The influence of clinical, pathological and surgical factors on the occurrence of recurrence of borderline ovarian tumors in different age groups - F. V. Novikov; V. P. Bondarev; E. S. Mishina; M. V. Mnikhovich (ABV-press, 2019)
Background. Borderline ovarian tumors (BOT), due to their unclear biological potential, remain a problem for oncogynecologists. On the one hand, frequent recurrences of tumors, and on the other hand, a high survival rate in the diagnosis of patients requires careful weighing of all risk factors when choosing surgical intervention tactics in patients with BOT. A large number of recurrences of BOT in patients of fertile age lead to disability of patients, deterioration of their quality of life and loss of reproductive function.Objective: evaluation of the influence of clinical and morphological factors (the presence of non-invasive implants, bilateral lesion of the ovaries, the presence of psammous bodies and malignization tricks) and surgical factors (damage to the cyst capsule and carrying out fertility preserving operations) on the recurrence of BOT in various age groups.Materials and methods. The material for the study was the protocols of an in vivo pathoanatomical study of a biopsy (surgical) material obtained from patients with a diagnosis of BOT for the period from 2000 to 2017 inclusive, according to the Regional Forensic Medical Bureau of Kursk. A total of 110 protocols for the first occurrence of BOT and 14 protocols for the tumor recurrences were analyzed. The age of patients undergoing an in vivo pathologic examination ranged from 19 to 75 years.Results and conclusions. It has been revealed that psammous bodies, fertility preserving operations and reproductive age are associated with tumor recurrence. Groups of patients with foci of malignancy and bilateral lesions have a lower risk of BOT recurrence due to the radical surgical treatment tactics and possibly the use of chemotherapy in the first case. Non-invasive implants are not associated with the risk of BOT recurrence.